Electromagnetic Radiation Effects of Radio Frequency Source on the Human Body - Bouali Lazhar; Djennah Mohammed; Tahmi Redouane; Zahraoui Mahrez (Technological Innovation in Engineering Research Vol. 4, 2022)
The present study confirm energy dissipated in the human head, vary with the distance between the human head and the electromagnetic source, and with the variation of exterior medium parameters. The use of mobile phones is growing exponentially. Our problem is the electromagnetic field coupling between the radio frequency power source and the biological tissue (human head). To solve this problem, a system of equations placed and the choice of formulation of finite elements that coupled with the boundary integral formulation that adopts with the system. Knowledge of electromagnetic field at any point of interior medium and the surface obtained by an integral formulation, based on boundary integral method. With this method we can assess the RF energy at each point of the interior medium (human head), basing on the parameters of the exterior medium, we are able to choose the best material of the interface’s realization. The propagation of electromagnetic wave through the dielectric medium has correctly modeled and the use of the absorbing condition, which permits the analysis of the open field problem.